Theoretical study on photooxidation mechanism of ruthenium complex [Ru(II)‐(bpy)2(TMBiimH2)]2+ with molecular oxygen. Issue 24 (7th July 2016) - Liu, Li‐Hong; Wu, Dan; Xia, Shu‐Hua; Cui, Ganglong
Abstract : Photoinduced reactions of ruthenium complexes with molecular oxygen have attracted a lot of experimental attention; however, the reaction mechanism remains elusive. In this work, we have used the density functional theory method to scrutinize the visible‐light induced photooxidation mechanism of the ruthenium complex [Ru(II)‐(bpy)2 (TMBiimH2 )] 2+ (bpy: 2, 2‐bipyridine and TMBiimH2 : 4, 5, 4, 5‐tetramethyl‐2, 2‐biimidazole) initiated by the attack of molecular oxygen. The present computational results not only explain very well recent experiments, also provide new mechanistic insights. We found that: (1) the triplet energy transfer process between the triplet molecular oxygen and the metal‐ligand charge transfer triplet state of the ruthenium complex, which leads to singlet molecular oxygen, is thermodynamically favorable; (2) the singlet oxygen addition process to the S0 ruthenium complex is facile in energy; (3) the chemical transformation from endoperoxide to epidioxetane intermediates can be either two‐ or one‐step reaction (the latter is energetically favored). These findings contribute important mechanistic information to photooxidation reactions of ruthenium complexes with molecular oxygen. © 2016 Wiley Periodicals, Inc. Abstract : DFT electronic structure calculations shed important light on the visible‐light induced photooxidation mechanism of ruthenium complexes with molecular oxygen.